Notes on the bionomics of the prawn Metapenmus monoceros, Fabricius - George, M J (Indian Journal of Fisheries, 2016)
Metapenceus monoceros, Fabricius is one of the three species of Penaeids contributing to the commercial prawn fishery of the Cochin backwaters. The following notes have been prepared from a study of samples collected from both paddy field and backwater catches during the period 1952-55 and offshore trawl net catches during 1957. Samples of backwater catches were collected from places like Kumbalangi, near the southern end, Pallippuram at the northern end and Narakkal at about the middle of the Cochin backwaters. A total number of 15,899 specimens have been measured and studied during the period.